Administrative Discretion in Licensing Governance: A Qualitative Study of Legal Accountability - Didi Nursidi (International Journal of Science Education and Cultural Studies, 2024)
Administrative discretion in licensing governance is a form of modern bureaucratic practice, but it also carries the potential risk of serious legal accountability deviations. In the context of developing countries such as Indonesia, where the scope of public officials' authority is often not clearly defined , administrative freedom is often a paradoxical instrument: on the one hand, it allows the necessary governance flexibility to respond to diverse local conditions, but on the other hand, it has the potential to create loopholes for corruption, collusion, and nepotism in the licensing process. This study aims to investigate the pattern of administrative discretion in licensing governance in Indonesia, identify factors that influence the legal accountability of public officials in the use of discretion, and formulate an analytical framework for legal accountability based on the local institutional context. The study uses an empirical juridical approach with a qualitative method based on grounded theory. Data collection was conducted through in-depth interviews with 48 participants consisting of licensing officials, administrative law experts, business actors, and members of the supervisory commission, as well as analysis of primary legal documents and focus group discussions (FGDs) as triangulation of findings. Data were analyzed using a thematic analysis framework and a layered legal accountability matrix. The findings indicate that administrative discretion in licensing governance in Indonesia is multidimensional and influenced by six determinant factors: regulatory clarity, human resource capacity of officials, local political pressure, internal oversight mechanisms, bureaucratic organizational culture, and accessibility of administrative justice. This study produces a legal accountability model of administrative discretion based on institutional context that can be a reference for licensing system reform in Indonesia.